The Urgency of the Role of Officials Making Land Deeds in the Protection of Disputed Land Buyers - Dirgantari, Yuni (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The Indonesian state is basically a constitutional state, guaranteeing the recognition, respect and protection of land ownership rights. However, this is not going well in reality, this is due to the legal culture of the people who often do not heed existing laws. This situation can be seen in various kinds of land disputes between buyers and sellers or buyers with third parties related to the land seller. The role of the Notary/PPAT required has not been able to be realized optimally. This article uses the empiric method. Based on the studies conducted, it can be seen that the role of the Notary/PPAT in protecting disputed land buyers in Kendari City is currently not optimal.Keywords: Buyer; Disputed; Protection.